1971
DOI: 10.46429/jaupr.v55i4.11009
|View full text |Cite
|
Sign up to set email alerts
|

Whitefly-Transmitted Viruses in Puerto Rico

Abstract: The viruses transmitted by the Puerto Rican whitefly (Bemisia tabaci Genn.), their vectors, and their main hosts are discussed in the present paper. The possible relationships between some of these viruses and certain foreign rugaceous viruses also are discussed. It seems that the Rhynchosia mosaic (Puerto Rico), the yellow mosaic of Phaseolus lunatus L. (India) and the yellow mosaic of Phaseolus longepedunculalus Mart. (Brazil) are related diseases. The Puerto Rican mosaic of Sida carpinifolia also seems rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the exact bounds of distinct species are yet indeterminate, particularly because of the difficulty in proving species separation as defined by the biological species concept in field populations of B. tabaci . Despite the varied and evolving interpretations of B. tabaci species status over the years, many studies have demonstrated biological differences among cryptic B. tabaci , including, among others, host range [ 80 ], insecticide resistance [ 81 ], virus transmission [ 82 ], and composition of endosymbionts [ 39 ].…”
Section: Whitefly Endosymbiont Evolution and Diversitymentioning
confidence: 99%
“…However, the exact bounds of distinct species are yet indeterminate, particularly because of the difficulty in proving species separation as defined by the biological species concept in field populations of B. tabaci . Despite the varied and evolving interpretations of B. tabaci species status over the years, many studies have demonstrated biological differences among cryptic B. tabaci , including, among others, host range [ 80 ], insecticide resistance [ 81 ], virus transmission [ 82 ], and composition of endosymbionts [ 39 ].…”
Section: Whitefly Endosymbiont Evolution and Diversitymentioning
confidence: 99%